Protocols with blood flow restriction during resistance training: a systematic review - Camila Papini; Nuno Sousa; Danilo Bertucci; Natália Bertolini; Leandro Acedo; Sebastião Gobbi (Revista Brasileira de Atividade Física e Saúde)
This systematic review investigated protocols used in Blood Flow Restriction (BFR) exercise training and evaluated the intensity of exercise and length of training for the development of muscle hypertrophy and strength. Twelve studies were included according to criteria. The Random-effects Model was used to teste the intensity of exercise and length of training in quadriceps femoral. In general, the BFR group was associated with an increase in Muscle Cross-sectional Area (CSA) of 3.84%; however, it was not associated with an increase in quadriceps strength compared with the control group. When the analyses were made considering the intensity of the exercise and length of training, the results showed that BFR exercise ≤ 30% of One Repetition Maximal (1RM) and the length of training ≤ 2 weeks were associated with an increase in quadriceps CSA and strength compared with the control group. The analyses provide subsidies that BFR training until 30% 1RM and a length of training until 2 weeks are the most effective to develop muscle hypertrophy and strength in lower limbs than exercise more than 30%1RM and more than 4 weeks of length training.